A multidisciplinary intervention to reduce central line-associated bloodstream infection in pediatrics and neonatal intensive care units - Wafaa Seddik Hamza; Esam Ahmed-Taher Mahmoud Hamed; Mariam Abdelrahman Alfadhli; Moustapha Ahmed-Maher Ramadan (Elsevier, 2022)
Background: To date, central line-associated bloodstream infections (CLABSIs) are the most common healthcare-associated infections in high-risk neonates and children. These infections are associated with significantly longer hospital stays, increased health care cost, and mortality in the health care systems. Application of evidence-based preventive interventions has proven to decrease CLABSI rate. The purpose of this study is to reduce the undesired relative high CLABSI rate through the adoption of standardized quality improvement interventions. Methods: and Methods: The study employed a pre-post-intervention design. Phase one is a retrospective calculation of 12 months of surveillance period as a baseline. Phase 2 establishes a multidisciplinary quality improvement intervention, which includes the formation of a dedicated central line insertion team, provision of central line kit at the bedside, training and educating the team, and selecting bundle checklist. In the third phase, we performed auditing and calculating the checklist compliance and monthly feedback for 12 consecutive post-intervention months. During phase 1 and 3, we calculated the following measures; CLABSI per 1000 catheter-days, duration of central line use, and device utilization ratio. Results: During the post-intervention phase the CLABSI rate significantly reduced by 59.5% from 7.5 to 3.0 per 1000 central line day, and the duration of use of the central line decreased from 21.3 ± 9.9 to 11.0 ± 3.2 days (P < 0.05). Conclusion: Implementation of quality improvement multidisciplinary intervention; central line insertion and maintenance care bundle, dedicated IV team, education and feedback effectively reduced the rate of CLABSI within our pediatrics and neonatal ICUs.